The Emerging Roles of Gamma–Delta T Cells in Tissue Inflammation in Experimental Autoimmune Encephalomyelitis - Malik, Sakshi; Want, Muzamil Yaqub; Awasthi, Amit (Frontiers in Immunology, 2016)
γδ (gamma delta) T cells, a small population of unconventional T cells, have been seen in central nervous system (CNS) lesions of multiple sclerosis (MS) patients, but their function in disease activity is not clearly understood. Previous studies in experimental autoimmune encephalomyelitis (EAE) were inconsistent in identifying their specific roles in suppressing or promoting disease pathogenesis. Emerging advancements in the biology of γδ T cells especially in the context of their being the major initial producers of IL-17 suggested their crucial role in pathogenesis of EAE. In addition, γδ T cells express high levels of IL-23R and IL-1R, which further enhance their effector functions in the pathogenesis of EAE. Nonetheless, activation of heterogeneous γδ T cells display functional dichotomy, which is crucial in determining the outcomes of tissue inflammation in EAE. In this review, we discussed recent advances in understanding the biology of γδ T cells in tissue inflammation as well as their roles in suppressing or promoting the development of EAE.